Crazy Little Thing Called Sox-New Insights in Oligodendroglial Sox Protein Function - Wittstatt, Jan; Reiprich, Simone; Küspert, Melanie (International Journal of Molecular Sciences, 2019)
In the central nervous system, oligodendrocytes wrap axons with myelin sheaths, which is essential for rapid transfer of electric signals and their trophic support. In oligodendroglia, transcription factors of the Sox protein family are pivotal regulators of a variety of developmental processes. These include specification, proliferation, and migration of oligodendrocyte precursor cells as well as terminal differentiation to mature myelinating oligodendrocytes. Sox proteins are further affected in demyelinating diseases and are involved in remyelination following damage of the central nervous system. Here we summarize and discuss latest findings on transcriptional regulation of Sox proteins, their function, target genes, and interaction with other transcription factors and chromatin remodelers in oligodendroglia with physiological and pathophysiological relevance.
CRIS-Team Scopus Importer:2019-06-21
Keywords: glia; myelin; oligodendrocyte; Sox protein; transcription factor